Maternal-Fetal Interplay in Zika Virus Infection and Adverse Perinatal Outcomes - Teixeira, Franciane Mouradian Emidio; Pietrobon, Anna Julia; Oliveira, Luana de Mendonça; Oliveira, Luanda Mara da Silva; Sato, Maria Notomi (Frontiers in Immunology, 2020)
During pregnancy, the organization of complex tolerance mechanisms occurs to assure nonrejection of the semiallogeneic fetus. Pregnancy is a period of vulnerability to some viral infections, mainly during the first and second trimesters, that may cause congenital damage to the fetus. Recently, Zika virus (ZIKV) infection has gained great notoriety due to the occurrence of congenital ZIKV syndrome, characterized by fetal microcephaly, which results from the ability of ZIKV to infect placental cells and neural precursors in the fetus. Importantly, in addition to the congenital effects, studies have shown that perinatal ZIKV infection causes a number of disorders, including maculopapular rash, conjunctivitis, and arthralgia. In this paper, we contextualize the immunological aspects involved in the maternal-fetal interface and vulnerability to ZIKV infection, especially the alterations resulting in perinatal outcomes. This highlights the need to develop protective maternal vaccine strategies or interventions that are capable of preventing fetal or even neonatal infection.